Marketing in developing countries - Kindra, G.S. (New York [etc.] Routledge, 2015)
The articles in this collection discuss the role of marketing in development, and include case studies from various developing countries. They consider state enterprises, marketing education, birth control and comparative marketing models.
Keywords: Marketing; Desarrollo económico; Países en desarrollo; Libros electrónicos